1999
DOI: 10.1111/j.1745-9125.1999.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Gender Difference in Adolescent Delinquent Behavior: A Longitudinal Test of Mediating Mechanisms*

Abstract: The extent to which mediating mechanisms account for the gender difference in delinquency was tested on a sample of 2, 753 adolescents studied across three points in time. Results using structural equations modeling showed that males are more likely to be involved in delinquent activities, partly because they are less bound to conventional values, more likely to be associated with delinquent peers, and report more adverse experiences with the authorities. These effects remain after partialling out the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 17 publications
5
67
1
2
Order By: Relevance
“…In terms of commitment, Rosenbaum and Lasley (1990) affirmed that commitment was strongly related to male delinquency, while Dukes and Stein (2001) reported a stronger association of commitment with female than male delinquency, particularly with regards to school commitment (Friedman and Rosenbaum 1988). Similarly, organizational involvement (Huebner and Betts 2002;Rosenbaum and Lasley 1990) and belief in conventional norms (Liu and Kaplan 1999) were reported to have a stronger impact on female delinquency than on male delinquency.…”
Section: Gender and Social Control Theorymentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of commitment, Rosenbaum and Lasley (1990) affirmed that commitment was strongly related to male delinquency, while Dukes and Stein (2001) reported a stronger association of commitment with female than male delinquency, particularly with regards to school commitment (Friedman and Rosenbaum 1988). Similarly, organizational involvement (Huebner and Betts 2002;Rosenbaum and Lasley 1990) and belief in conventional norms (Liu and Kaplan 1999) were reported to have a stronger impact on female delinquency than on male delinquency.…”
Section: Gender and Social Control Theorymentioning
confidence: 95%
“…Some studies suggest that social bonds operate similarly for males and females in not only the deterrence of delinquency, but also the explanation of juvenile delinquency (e.g., Hartjen and Priyadarsini 2003;Huebner and Betts 2002). In particular, Liu and Kaplan (1999) asserted that social control theory is general enough to adequately explain both male and female offending (see also Naffine 1996).…”
Section: Gender and Social Control Theorymentioning
confidence: 99%
“…We control for parental education since parents with higher educational levels are more likely to work in state-owned work-units and thus are less likely to deviate from government regulation by having more than one child. Furthermore, children from more educated families are likely to be better adjusted such as by engaging less in delinquent activities and/or experiencing less psychological distress (Liu and Kaplan 1999a, b). We control for family income since adolescents from families with higher income levels are likely to have greater family resources, which is expected to alleviate distress and curb delinquency (Liu and Kaplan 1999a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Gender is considered since families with first-born girls may be inclined to having additional children than families with first-born boys (e.g., Chow and Zhao 1996), and gender is also a strong correlate of delinquent participation (Liu and Kaplan 1999a) and psychological distress (Liu and Kaplan 1999b). Similarly, students who are older and thus in higher grade level may be more likely to engage in delinquent activities, as age has been a known correlate of delinquency (e.g., Hirschi and Gottfredson 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that social control factors such as parental attachment, involvement in various pro-social activities, and belief in traditional norms affect both men's and women's reports of serious deviance and risky behavior (Booth et al 2008;Alarid et al 2000;Canter 1982;Liu & Kaplan 1999;Smith & Paternoster 1987). For example, there is a differentiated process of social bonding where girls, particularly in patriarchal households, have a lowered preference for risk through the acquisition of passive gender roles, placing the most importance on relational bonding (Chapple et al 2005).…”
Section: Gender and Social Control Theorymentioning
confidence: 99%